UV Spectrophotometric Determination of Clopidogrel and Repaglinide - Gowri Sankar, D.; Kalyan Sumanth, S.; Pawar, A.K.M.; Madhavi Latha, P.V. (Asian Journal of Chemistry, 2016)
Simple and sensitive UV spectrophotometric methods have been developed for the determination of clopidogrel and repaglinide in pure and pharmaceutical formulations. These methods obey Beer's law in the concentration ranges 10–60 and 5–25 μg/mL exhibiting maximum absorption at 225 and 220 nm respectively. The methods were extended to pharmaceutical formulations and there was no interference from common pharmaceutical additives and excepients.